2016
DOI: 10.17795/jhealthscope-27112
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Mental Health and Psychological Hardiness of the Staff at the Pars Special Economic Energy Zone in Iran: A Cross-Sectional Study

Abstract: Background: Psychological hardiness is a protective personality characteristic against life stresses that plays a major role in improving one's ability to cope with environmental pressures. Objectives: Thus, the present study aimed to evaluate the mental health status, psychological hardiness, and the correlation between the two in workers of the Pars special economic energy zone in 2010 with a special emphasis on demographic factors, such as age, sex, marital status, job status, field of action, and job exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The result of this study showed a significant relationship between psychological hardiness and perceived social support, which prevents psychological distress to deal with stress among women with breast cancer. It means that the higher the level of perceived social support, the higher the psychological hardiness of women with breast cancer, which was consistent with several other studies [10][11][12][13][14][15], and no study was found inconsistent with this finding. Abdollahi et al showed the significance of hardiness in decreasing perceived stress impacts on hope and reported its clinical implications for health practitioners [15].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The result of this study showed a significant relationship between psychological hardiness and perceived social support, which prevents psychological distress to deal with stress among women with breast cancer. It means that the higher the level of perceived social support, the higher the psychological hardiness of women with breast cancer, which was consistent with several other studies [10][11][12][13][14][15], and no study was found inconsistent with this finding. Abdollahi et al showed the significance of hardiness in decreasing perceived stress impacts on hope and reported its clinical implications for health practitioners [15].…”
Section: Discussionsupporting
confidence: 90%
“…These individuals' hardiness likely results from the perception of life changes as less stressful or having a higher capacity to cope with life changes. Several studies have indicated that psychological hardiness and social support are significant psychosocial factors for illness recovery [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations